2018
DOI: 10.3389/fimmu.2018.00306
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Interacting Protein Kinases 1 and 3, and Mixed Lineage Kinase Domain-Like Protein Are Activated by Sublytic Complement and Participate in Complement-Dependent Cytotoxicity

Abstract: The complement system participates in the pathogenesis of many diseases. Complement activation produces several active protein complexes and peptides, including the terminal C5b-9 complexes. It was reported that C5b-9 complexes insert into the plasma membrane and cause membrane perturbation, intracellular calcium surge, metabolic depletion, and osmotic lysis. Previously, we showed that complement-dependent cytotoxicity (CDC) is regulated by JNK and Bid. Here, we demonstrate that three mediators in TNFα-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 79 publications
1
24
0
Order By: Relevance
“…Treatment of neurons with NEVs and AEVs from 4 AD compared to 4 control participants resulted in a significantly increased EthD-1 fluorescence fold change over vehicle [For NEVs, F (1, 24.020) = 4.525, p = 0.044; AD vs. Normal, p = 0.044; for AEVs, F (1, 24.872) = 5.804, p = 0.024; AD vs. controls, p = 0.024], suggesting that AD NEVs and AEVs mediate neuronal membrane disruption; there were no differences in EthD-1 fluorescence over vehicle in neurons treated with CD81+ EVs (F (1, 31.429) = 0.969, p = 0.332) from AD compared to control participants. MAC-dependent cytotoxicity is accompanied by activation of the regulated necrosis pathway known as necroptosis, which involves phosphorylation of the mixed-lineage kinase domain-like protein (MLKL) (32,33). To further explore the mechanism of neurotoxicity induced by AEVs and NEVs, we evaluated whether EV-treated neurons exhibit necroptosis and apoptosis cell death markers.…”
Section: Neurotoxicity Of Ad Aevs Is Associated With Complement Mac Amentioning
confidence: 99%
“…Treatment of neurons with NEVs and AEVs from 4 AD compared to 4 control participants resulted in a significantly increased EthD-1 fluorescence fold change over vehicle [For NEVs, F (1, 24.020) = 4.525, p = 0.044; AD vs. Normal, p = 0.044; for AEVs, F (1, 24.872) = 5.804, p = 0.024; AD vs. controls, p = 0.024], suggesting that AD NEVs and AEVs mediate neuronal membrane disruption; there were no differences in EthD-1 fluorescence over vehicle in neurons treated with CD81+ EVs (F (1, 31.429) = 0.969, p = 0.332) from AD compared to control participants. MAC-dependent cytotoxicity is accompanied by activation of the regulated necrosis pathway known as necroptosis, which involves phosphorylation of the mixed-lineage kinase domain-like protein (MLKL) (32,33). To further explore the mechanism of neurotoxicity induced by AEVs and NEVs, we evaluated whether EV-treated neurons exhibit necroptosis and apoptosis cell death markers.…”
Section: Neurotoxicity Of Ad Aevs Is Associated With Complement Mac Amentioning
confidence: 99%
“…While mechanical stress has been shown to induce both primary necrosis and apoptosis [38,82], injury-related necroptosis was found in vivo [122] but seemed to play a minor role in our ex vivo cartilage trauma models under serum-free conditions [113]. We concluded that the activation of the necroptotic pathway might require further co-factors, such as TNFa or certain serum-components [109,123], and concurrent inhibition of the caspase cascade [113]. However, we could provide evidence that necroptosis occurs in highly degenerated human cartilage, implying a potential role of necroptosis in OA disease [113].…”
Section: Chondrocyte Death and Cluster Formationmentioning
confidence: 74%
“…The cells were cultured in DMEM/F12 medium (Gibco Life Technologies, Carlsbad, CA, USA) containing 10% FBS (HyClone, U.S.) supplemented with 1% penicillin and streptomycin (Beyotime, Shanghai, China) in a humidified incubator with 5% CO2 at 37˚C. Cells were grown to 70-80% confluency and stimulated with AngII (Sigma, USA) at a concentration range of 10 −10 -10 −5 M for 24 h and exposed to 10 −9 M AngII for 12 h, 24 h, 36 h, 48 h, and 72 h. To further assess the necroptosis of HK-2 cells, cells were pretreated with RIP1 inhibitor (100 μM Nec-1 [5]) or the pan-caspase inhibitor (10 mM zVAD [5]) for 30 min, RIPK3 blocker (0.25 μM GSK'872 [19]) or MLKL inhibitor (1 μM NSA, Selleck, USA [8]) for 1 h. To elucidate the relevant mechanisms, cells were treated with an AT1R antagonist (10 μM losartan [20,21]) and an AT2R antagonist (PD123319 [20,21]) for 30 min or with FasL inhibitor (3 μg/ml [22,23] the neutralizing Human Fas Ligand/TNFSF6 Antibody (RD Systems, USA)) for 2 h. After pretreatment for the assigned duration, HK-2 cells were exposed to 10 −9 M AngII for 24 h. The treated cells were collected at the assigned time for western blot analysis, TEM, and immunofluorescence staining.…”
Section: Cell Culture and Gene Expression Interferencementioning
confidence: 99%